1997
DOI: 10.1161/01.cir.96.6.1964
|View full text |Cite
|
Sign up to set email alerts
|

Raloxifene Inhibits Aortic Accumulation of Cholesterol in Ovariectomized, Cholesterol-Fed Rabbits

Abstract: Our findings indicate that raloxifene hydrochloride has a potentially important antiatherogenic effect, analogous to that observed with estrogen in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(62 citation statements)
references
References 28 publications
5
54
0
3
Order By: Relevance
“…13,29 Second, raloxifene inhibits the accumulation of cholesterol in ovariectomized cholesterolfed rabbits and inhibits macrophage lipid oxidation. 30,31 Third, raloxifene acutely dilates rabbit coronary arteries via NO-and calcium influx-dependent pathways and increases uterine and coronary blood flow in ovariectomized ewes. 14,32 However, it has not yet been elucidated whether long-term treatment with raloxifene leads to reduced blood pressure and improved vascular function in hypertensive males.…”
Section: Discussionmentioning
confidence: 99%
“…13,29 Second, raloxifene inhibits the accumulation of cholesterol in ovariectomized cholesterolfed rabbits and inhibits macrophage lipid oxidation. 30,31 Third, raloxifene acutely dilates rabbit coronary arteries via NO-and calcium influx-dependent pathways and increases uterine and coronary blood flow in ovariectomized ewes. 14,32 However, it has not yet been elucidated whether long-term treatment with raloxifene leads to reduced blood pressure and improved vascular function in hypertensive males.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, the chemical structure of raloxifene differs considerably from that of tamoxifen, and the effects of raloxifene on atherosclerosis are uncertain. 10,11 Droloxifene is a structural analogue of tamoxifen with tissue-specific estrogen agonistic/antagonistic effects. 12 In ovariectomized rodents, it prevents bone loss and lowers cholesterol without causing uterine hypertrophy.…”
mentioning
confidence: 99%
“…41 Multiple animal studies have demonstrated that raloxifene reduces the size of atherosclerotic lesions, 8,9 and pursuant to these other studies, perhaps the marginal changes in lipid parameters (LDL reduction, HDL elevation) may have contributed to the differences in lipid deposition seen in this experiment. Alternatively, the atheroma regression may have occurred completely independent of systemic cholesterol levels and may have been mediated via the anti-inflammatory effects seen in vascular wall.…”
Section: Discussionmentioning
confidence: 74%
“…6,7 The mechanism of raloxifene's potential effects upon atherosclerotic lesions is not completely understood. Pre-clinical animal models have shown that raloxifene, similar to HT, inhibits atherosclerosis, 8,9 but its effect upon vascular calcification is unknown. HT results in less calcified plaques 10 without clear reduction in cardiovascular events, 11 yet statins, a therapy with clear reductions in cardiovascular events, increase calcification.…”
mentioning
confidence: 99%